2019
DOI: 10.1177/1559827619866815
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of the Role of Mindfulness Practices in Nutrition for Mothers and Their Children

Abstract: Nutrition-related problems have been increasingly prevalent among children and adults nationally and globally. Pregnant women and children are particularly susceptible to nutrition-related concerns. Mindfulness-based programs have demonstrated favorable outcomes for lifestyles and behaviors and may, therefore, assist in nutrition-related concerns. This column focuses on existing literature that focuses on the way mindfulness practices improve eating and nutrition outcomes for mothers. The synthesized findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The nding of the study indicated feeding by mother reducing odd of undernutrition and feeding by caregiver increasing odd of undernutrition as compared with mother. Which was inconsistent with a study which stated Children feeding practice done by mother were effective which is resulting for improvement of nutritional status (35). Nevertheless, it has disagreed with the study conducted in Indonesia which said there were no signi cant associations between the role and knowledge of the mothers and adequate nutritional status of their infants and toddlers (36).…”
Section: Discussionmentioning
confidence: 88%
“…The nding of the study indicated feeding by mother reducing odd of undernutrition and feeding by caregiver increasing odd of undernutrition as compared with mother. Which was inconsistent with a study which stated Children feeding practice done by mother were effective which is resulting for improvement of nutritional status (35). Nevertheless, it has disagreed with the study conducted in Indonesia which said there were no signi cant associations between the role and knowledge of the mothers and adequate nutritional status of their infants and toddlers (36).…”
Section: Discussionmentioning
confidence: 88%